2022
DOI: 10.3390/youth2020014
|View full text |Cite
|
Sign up to set email alerts
|

Issues Concerning the Interpretation and Assessment of Career Adaptability: Perspective from Hong Kong, China

Abstract: The concept of career adaptability has been widely applied across cultural and educational settings in the hope of finding working solutions to facilitate school-to-work transition. In Hong Kong, China, there are signs showing that career adaptability scores are increasingly being used as the dominant benchmark to measure the effectiveness of career interventions designed for student populations. However, this concept is developed primarily based on western values. For it to fulfill its theoretical promises, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…These evaluation results would be valuable recourses for school stakeholders’ development of productive career guidance activities to support students with diverse needs in Hong Kong and other countries/regions. As Wong (2022) argued in a review of career adaptability, given that this contract was typically developed in Western cultures, cross-cultural empirical studies, as well as appropriate interpretations of career adaptability concerning local contexts of different research designs, need to be recognized and strengthened.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These evaluation results would be valuable recourses for school stakeholders’ development of productive career guidance activities to support students with diverse needs in Hong Kong and other countries/regions. As Wong (2022) argued in a review of career adaptability, given that this contract was typically developed in Western cultures, cross-cultural empirical studies, as well as appropriate interpretations of career adaptability concerning local contexts of different research designs, need to be recognized and strengthened.…”
Section: Discussionmentioning
confidence: 99%
“…However, Salimi et al (2022) did not examine the factor structure and the four dimensions of career adaptability. In a recent review conducted by Wong (2022) , this scholar reviewed 463 published studies on career adaptability in a range of disciplines of psychology and found that “most published studies in Hong Kong on career adaptability did not use data and methodological triangulation research methodologies” (p. 181).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Career construction theory and career adaptability may contain different dimensions in China compared to elsewhere that reflect Chinese cultural values [74]. A recent review study showed that flexibility and creativity are essential career adaptability resources in Chinese culture [75], which presents an opportunity to design an appropriate career adaptability measurement according to the cultural context in China. Researchers should also consider parental influence (e.g., parents' education and occupation), an essential factor in adolescents' career construction in Chinese culture.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…On one hand, in terms of life-long learning, it is important to update knowledge and acquire new abilities continuous to increase one’s career development potential. On the other hand, it can boost one’s confidence and gain more sense of assertiveness ( Wang, 2021 ). Therefore, organizing “small group” training not only improves the professional ability of employees, but also promotes the spirit of learning from each other.…”
Section: Suggestionmentioning
confidence: 99%